A study of fatty acid composition and tocopherol content of lipid extracted from marine microalgae, Nannochloropsis oculata and Tetraselmis suecica, using solvent extraction and supercritical fluid extraction - Bong, S. C.; Loh, Su Peng (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
This study was conducted to investigate and compare the fatty acids and tocopherols of lipid extracted from marine microalgae, Nannochloropsis oculata (NO) and Tetraselmis suecica (TS) using solvent extraction and supercritical fluid extraction (SFE). Fatty acids and tocopherols were determined in the extracted lipid as functions of the temperature (40, 80°C) and pressure (3000, 5000, 7000, 9000psi). Dichloromethane/methanol and hexane were the chosen conventional solvent for fatty acids and tocopherols extraction respectively. The results obtained showed that there were differences in the fatty acid composition of various lipid extracts of NO and TS. Extracts of NO were high in myristic acid (C14:0) (17-35%), palmitic acid (C16:0) (14-47%) and palmitoleic acid (C16:1) (11-42%) whereas extracts of TS were high in C14:0 (21-34%) and C16:0 (29-49%). Eicosapentaenoic acid (EPA) was detected only under certain SFE conditions in NO but was not detected in TS. α-, β- and γ-tocopherol were detected in various SFE extracts of NO but only α- and β-tocopherol were detected in TS. Hexane extraction of both NO and TS resulted in the detection of only α-tocopherol. In conclusion, the use of different extraction methods resulted in different compositions and concentrations of fatty acids and tocopherols in the microalgae studied.